PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR IPS DI SDN 20 PONTIANAK SELATAN - Dzulkarnain, Dzulkarnain; Marli, Suhardi; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aimed to know the influence of mind mapping learning model students?s learning outcome in social science grade V Elementary School state of 20 South Pontianak . This research has been used experiment method with quasi experiment and design research was nonequivalent control group design. Result research obtained average result of post-test control class is 62 and the avarege result of post-test experimental class is 68,14. Test result of t-test got thitungamounted to 2,2327 and ttabel (? = 5% with dk = 49) amounted to 1,6794 that is meant thitung (2,2327) > ttabel (1,6794), so Ha is received. The conclusion exists influence mind mapping learning model students?s learning outcome in social science grade V Elementary School state of 20 South Pontianak. The counting of effect size (ES), got ES amounted ti 0,75 (high category).Key Words : Influence, Mind Mapping Learning Model , Learning Outcome, Social Science